THE ROLE OF THE INTERNET IN THE LIFE OF YOUTH AND THE PRACTICAL SIGNIFICANCE OF HISTORICAL CHRONOLOGICAL DEVELOPMENT (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the role of the Internet in the lives of young people, its historical and chronological stages of development, and its practical significance in modern society. The scientific basis of the impact of the Internet on the worldview, learning methods, social activity, and communication skills of young people is covered. It also discusses the positive and negative aspects of the introduction of internet technologies into the lives of young people. The study provides conclusions on the effective use of the Internet and its role in the development of young people.
Keywords: Internet, youth, digital technologies, information society, historical development, social networks, education, communication, globalization, media literacy.